TGR5 Regulates Macrophage Inflammation in Nonalcoholic Steatohepatitis by Modulating NLRP3 Inflammasome Activation - Shi, Yong; Su, Wantong; Zhang, Lei; Shi, Chengyu; Zhou, Jinren; Wang, Peng; Wang, Hao; Shi, Xiaoli; Wei, Song; Wang, Qi; Auwerx, Johan; Schoonjans, Kristina; et al. (Frontiers in Immunology, 2021)
Nonalcoholic steatohepatitis (NASH) is a chronic liver disease associated with dysregulation of liver metabolism and inflammation. G-protein coupled bile acid receptor 1 (TGR5) is a cell surface receptor that is involved in multiple metabolic pathways. However, the functions of TGR5 in regulating macrophage innate immune activation in NASH remain unclear. Here, we found that TGR5 expression was decreased in liver tissues from humans and mice with NASH. Compared to wild type (WT) mice, TGR5-knockout (TGR5−/−) mice exhibited exacerbated liver damage, increased levels of proinflammatory factors, and enhanced M1 macrophage polarization. Moreover, TGR5 deficiency facilitated M1 macrophage polarization by promoting NLRP3 inflammasome activation and caspase-1 cleavage. Taken together, our findings revealed that TGR5 signaling attenuated liver steatosis and inflammation and inhibited NLRP3-mediated M1 macrophage polarization in NASH.